PENGARUH GAME EDUKASI WORDWALL TERHADAP MINAT BELAJAR SISWA KELAS V MI. YAA BUNAYYA FATHUL KHAIR - Muhajir; Asia, Nur; Sukida; Regita Maulinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to determine if using online word games as a learning tool influences the motivation of students at MI Yaa Bunayya Fatkhul Khair. Employing a quantitative approach, it includes a noncomparable pretest and posttest for the control group. The sample comprises 38 fifth-grade students, split into 19 students in class V A and 19 in class V B. Analysis of the hypothesis using an independent T test reveals a sig value of 0.000, indicating a response of <0.05. Thus, it can be concluded that the online game Wordwall significantly boosts the learning interest of fifth-grade students at MI Yaa Bunayya Fatkhul Khair.